(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
Maqsud Shaykhzada was a great poet, and we inherited his remarkable works. Let us get acquainted with the warm opinions of famous figures about him.